Preparation of MoNbTaW refractory high entropy alloy powders by pressureless spark plasma sintering: Crystal structure and phase evolution. (August 2020) - Han, Jiesheng; Su, Bo; Lu, Jinjun; Meng, Junhu; Zhang, Aijun; Wu, Youzhi
Abstract: This paper presents a novel method for preparing MoNbTaW refractory high entropy alloy (RHEA) powders. A porous MoNbTaW RHEA was firstly prepared by pressureless spark plasma sintering from pure elemental powders of Mo, Nb, Ta, and W, and then it was ball milled to achieve the RHEA powders. The sintering behavior, crystal structure, and phase evolution of the RHEA were studied by SEM, XRD, and TEM. The MoNbTaW RHEA with a single BCC phase was obtained at a sintering temperature far below melting points of the elements. The formation of MoNbTaW RHEA was a dynamic process through which a continuous solid solution formed due to atomic diffusion. The elemental atoms migrated and dissolved in a sequence of Mo→Nb→Ta→W. At the same temperature, the element with low cohesive energy diffused and dissolved prior to those with high cohesive energy. A TFDC model was also proposed to calculate the lattice constants of MoNbTaW RHAEs. In comparison, the lattice constants of MoNbTaW RHEAs calculated by the TFDC model were more accurate than those were calculated by Vegard's law. The results provide an efficient method for the preparation of RHEA powders and an accurate method to calculate lattice constants of HEAs. Graphical abstract: Image 1 Highlights: A novel method using pressureless spark plasma sintering and ball milling is demonstrated to prepare MoNbTaW RHEA powders. The formation of MoNbTaW RHEA is a dynamic process through which a continuous solid solution is formed. The elemental atoms migrate and dissolve in a sequence of Mo .→ Nb → Ta → W. A TFDC model is proposed to accurately calculate the lattice constants of HEAs.